Persuasive Communication Ability of Madrasah Principals in Improving Teacher Loyalty at MTS Nurul Amaliyah Tanjung Morawa - Aisyahrani, Adilla; Chaniago, Nasrul Syakur (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2025)
This study examines the role of persuasive communication by madrasah principals in building teacher loyalty in Islamic educational institutions. Using a qualitative approach and case study design, this research was conducted over three months at MTs Nurul Amaliyah Tanjung Morawa, which was selected for its efforts to strengthen teacher commitment through planned communication strategies. Data were collected from 11 purposively selected informants comprising the school principal, eight teachers, and two educational staff through in-depth interviews, participatory observation, and document analysis. Analysis was conducted using a thematic approach to identify key patterns related to persuasive communication strategies and their impact on teacher loyalty. Data validity was ensured through triangulation of sources, methods, and theory, referencing McCroskey & Richmond's persuasive communication theory, organisational loyalty, and transformational leadership. Findings indicate that the madrasah principal's empathetic, dialogic, and consistent communication significantly enhances teachers' emotional commitment, mutual respect, and professional trust. These practices also contribute to forming a collaborative and value-oriented school culture. This study enriches the existing literature by presenting a contextual model of persuasive leadership communication, particularly through personal interactions and participatory decision-making. Practically, it is recommended that persuasive communication training be integrated into school leadership development programs, especially in environments that emphasise moral and relational leadership. This study also opens opportunities for further research, including longitudinal and comparative studies across school contexts. Persuasive communication is an additional skill and a key strategy in shaping a cohesive and committed educational community